2022
DOI: 10.37467/revhuman.v11.3991
|View full text |Cite
|
Sign up to set email alerts
|

Análisis bibliométricos en publicaciones científicas sobre turismo sostenible en las universidades

Abstract: Este estudio presenta un análisis bibliométrico de un total de 113 publicaciones sacadas a la luz entre los años 1996 y 2021, que analizan la formación académica en materia sostenible en las universidades de turismo a nivel mundial. El principal objetivo de este análisis es identificar las investigaciones más relevantes en este campo y las tendencias más actuales de investigación en la base de datos de la Web of Science. Con este fin, efectuamos un examen de la productividad de los autores, revistas y regiones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…Through a density analysis based on mapping techniques (Van Eck & Waltman, 2018), we conclude that overall cooperation between researchers is relatively small in this area. This result suggests that sustainable education in tourism universities requires more research, as few academics have addressed it (León-Gómez & Mora Forero, 2022). Therefore, more researchers should consider contributing to the current debate (Camargo & Gretzel, 2017; Ochoa Jiménez et al, 2022; Sharma et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through a density analysis based on mapping techniques (Van Eck & Waltman, 2018), we conclude that overall cooperation between researchers is relatively small in this area. This result suggests that sustainable education in tourism universities requires more research, as few academics have addressed it (León-Gómez & Mora Forero, 2022). Therefore, more researchers should consider contributing to the current debate (Camargo & Gretzel, 2017; Ochoa Jiménez et al, 2022; Sharma et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Zhang, Xu, et al, 2022), but few have analysed the educational perspective of this relationship (Ochoa Jime´nez et al, 2022;Sharma et al, 2021). As a result, there is growing concerned about the need to teach sustainability within the curricula of tourism universities (Leo´n-Go´mez & Mora Forero, 2022). As Skill Theory states (Amanchukwu et al, 2015), the knowledge and skills students can acquire will be crucial to raising awareness among future tourism professionals of the importance of establishing sustainable practices in the sector (Barber et al, 2011).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…First, we conducted a bibliometric analysis, combining different methods to analyse a body of research (Santos-Jaén et al 2021;León-Gómez and Mora Forero 2022). These methods rely on descriptive publication data on authors, journals, institutions, geographical regions, keywords, and citations to generate networked knowledge maps within a research field to identify research topics and future research directions (Zhang et al 2022).…”
Section: Methodsmentioning
confidence: 99%
“…The literature on the topic of tourism sustainability has grown significantly in recent years, as evidenced by a search for articles utilizing the keywords "tourism", "sustainability" and "bibliometric analysis" in Scopus and the Web of Science (WoS) databases. As of 28 January 2023, a total of 53 articles were found that addressed various aspects of tourism sustainability, such as over-tourism [2], corporate social responsibility [3,4], community participation [5], sharing economy [6], sustainability education [7], sustainability in hospitality and tourism [8], tourism management and marketing [9], and tourism entrepreneurship [10,11]. This indicates a growing interest in the field of tourism sustainability and highlights the need for further examination of the literature in this area.…”
Section: Literature Reviewmentioning
confidence: 99%